Infrastrutture verdi urbane ed offerta di servizi ecosistemici: uno studio sulla Functional Urban Area della Città di Cagliari - Isola, Federica; Lai, Sabrina; Leone, Federica; Zoppi, Corrado (Contesti. Città, territori, progetti, 2026)
Urban green infrastructure (UGI) is an interconnected system of natural and semi-natural spaces, such as green areas, open spaces, and water features, which are strategically planned to provide ecosystem services and address community needs. UGIs should be inclusive and enhance human well-being, supporting biodiversity and facilitating access to natural resources. This study introduces a methodological framework for identifying UGIs, based on a taxonomic analysis of key ecosystem services (ES) essential to urban quality, including outdoor recreation, flood risk management, carbon capture and storage, habitat quality, and climate regulation. Furthermore, UGIs are modelled as complex networks composed of core areas, and urban ecological corridors. This approach is applied to the Functional Urban Area (FUA) of Cagliari in Italy. The findings indicate that areas with high levels of climate regulation, carbon storage and habitat quality are particularly well-suited for inclusion in UGI. While recreational potential is comparatively lower, it remains locally significant. On the other hand, flood mitigation zones demonstrate reduced connectivity due to urban impermeable surfaces.